Assurance and Evaluation Method for Reliability Requirements Completion of Aviation Product Based on CMM. (May 2019) - Li, Yuan; Wang, Wei; Feng, Weijia; Zhang, Qi; Liu, Huichao
Abstract: Modern aviation product needs to meet the reliability requirements during the development process. In this paper, a comprehensive assurance system of reliability requirements completion is established and a method to evaluate the assurance system capabilities of reliability requirements completion based on CMM (Capability Maturity Model) is proposed. The evaluate index system in each level is described and AHP method is applied to determine the weight of each index factor in maturity. The evaluation results can comprehensively and effectively direct the aviation product reliability work during the development process and ultimately ensure the reliability of aviation product meets the requirements.